The foreign policy of the second Trump administration: intentions and capabilities - Baichorov, Aleksandr M. (Journal of the Belarusian State University. International Relations, 2025)
This article challenges the prevailing view that the second Trump administration’s foreign policies are merely provocative and unpredictable. Several key characteristics of its international approach were already evident during D. Trump’s first term, others were shaped by enduring US interests, available resources, and the new geopolitical context after 2022. Understanding the shifts in Washington’s international approach requires examining D. Trump’s stated intentions and capabilities. By early 2025, at least four intentions had become apparent: expanding US-controlled territories, containing the influence of China, brokering a ceasefire in the Russia – Ukraine special military operation, and compelling allies to increase their financial and strategic contributions to Western defence. The administration deploys four primary capabilities to advance these goals: America’s substantial technological advantages, extensive financial and economic resources, soft power through free-market ideology, and military strength encompassing conventional forces and nuclear deterrence. When viewed through this framework of intentions and capabilities, D. Trump’s foreign policy appears considerably more coherent.
Keywords: US foreign policy; US; EU; China; collective West; political confrontation; consensus; global challenge; national economy; world economy; economic growth; containment policy; export; import; world markets; Taiwan; Russia; Ukraine; military operation; democracy; tariffs